easyCLIP analysis of RNA-protein interactions incorporating absolute quantification - Douglas F. Porter (Nature Portfolio, 2021)
It is important to develop quantitative criteria to identify RNA-binding proteins and target RNAs. Here, the authors present a method to quantify cross-linking and apply it to recurrent cancer mutations in RNA-binding proteins.